The Association Between Related Party Transaction And Tax Avoidance In Indonesia - Putra Aryotama; Amrie Firmansyah (AFEBI Accounting Review, 2019)
This study aims to examine the association between related party transaction and tax avoidance in Indonesia’ Non-Financial Companies. Related-party transactions, as its name implies, are transactions conducted by companies with its related parties. Meanwhile, tax avoidance is a reduction in corporate tax liability, which is conducted by the company legally. This study employs a quantitative method using linear regression analysis and uses panel data of companies listed under the Indonesia Non-Financial Companies on IDX from 2014 to 2017. The result of this study suggests that related party transaction is negatively associated with tax avoidance.